Correction: Štorkánová et al. Inhibition of Hsp90 Counteracts the Established Experimental Dermal Fibrosis Induced by Bleomycin. Biomedicines 2021, 9, 650 - Štorkánová, Hana; Štorkánová, Lenka; Navrátilová, Adéla; Bečvář, Viktor; Hulejová, Hana; Oreská, Sabína; Heřmánková, Barbora; Špiritović, Maja; Bečvář, Radim; Pavelka, Karel; Vencovský, Jiří; Distler, Jörg H W; et al. (Biomedicines, 2023)
In the original publication [...].